GENE-11. SMALL TERMINAL ALTERATIONS AND ALTERNATIVE LENGTHENING OF TELOMERES ARE A FEATURE OF IDH-MUTANT, 1p/19q NON-CODELETED GLIOMAS. (5th November 2018) - Brown, Desmond; Yamada, Seiji; Praska, Corinne; Kollmeyer, Thomas; Jacobs, Joshua; Decker, Paul; Kosel, Matt; Caron, Alissa; Halder, Chandralekha; Ruiz, Vanessa; Kipp, Benjamin; Voss, Jesse; et al.
Abstract: INTRODUCTION: Gliomas are typified by genetic variability and instability. The full potential of molecular genetics to classify tumors has not been realized. We previously proposed a novel glioma classification system that increases the sensitivity and specificity of diagnosis and improve prognostication. We have completed copy number array mutational analyses and a targeted next-generation sequencing 50-gene glioma panel on 148 Mayo Clinic formalin-fixed paraffin-embedded gliomas with subsequent data validation performed on 419 gliomas from the TCGA. RESULTS: Median age at resection was 49 years (range: 17–80; 95% CI: 46.5–51.6 years). There were 36 (24.3%) IDH-mutant, 1p/19q codeleted oligodendrogliomas; 46 (31.1%) IDH-mutant, 1p/19q non-codeleted astrocytomas and 66 (44.6%) IDH-wildtype gliomas. Small terminal alterations (STAs) defined as copy number variations (CNVs) IDH-mutant, 1p/19q non-codeleted tumors. Acquisition of 3 2 STAs was observed in 47% IDH-mutant, 1p/19q non-codeleted versus 27% IDH-wildtype tumors (P=1.8x10 -5 ). In the TCGA dataset, these were seen in 67% versus 26% respectively (P=2.8x10 -16 ). STAs were glioma subclass-specific and did not correlate with overall genetic instability as determined manually or with a computational method. ATRX loss was observed in 27 of 41 (65.9%) tumors with an ATRX mutation versus 20 of 106 (18.9%) ATRX-wildtype tumors (P=1.3x10 -7 ). ATRX loss also correlated with the alternative lengthening of telomeres (ALT) phenotype and was seen in 25 of 31 (80.6%) ALT-positive versus 7 of 55 (12.7%) ALT-negative tumors (P=1.5x10 -9 ). STAs were present in 19 of 32 (59.4%) ALT-positive cases and 8 of 35 (22.9%) ALT-negative cases (P=0.0061). CONCLUSION: IDH-mutant, 1p/19q non-codeleted astrocytomas have a high prevalence of STAs. This is associated with ATRX loss and the ALT. These alterations do not appear to have de novo implications for survival but may provide novel diagnostic tools and therapeutic targets.